High resolution time-to-space conversion of sub-picosecond pulses at 155µm by non-degenerate SFG in PPLN crystal - Shayovitz, Dror; Herrmann, Harald; Sohler, Wolfgang; Ricken, Raimund; Silberhorn, Christine; Marom, Dan M. (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Characteristics of displaced single photons attained via higher order factorial moments - Laiho, Kaisa; Avenhaus, Malte; Silberhorn, Christine (New Journal of Physics)
Keywords: General Physics and Astronomy

Collective Effects in Second-Harmonic Generation from Split-Ring-Resonator Arrays - Linden, S.; Niesler, F. B. P.; Förstner, Jens; Grynko, Yevgen; Meier, Torsten; Wegener, M. (Physical Review Letters)
Optical experiments on second-harmonic generation from split-ring-resonator square arrays show a nonmonotonic dependence of the conversion efficiency on the lattice constant. This finding is interpreted in terms of a competition between dilution effects and linewidth or near-field changes due to interactions among the individual elements in the array.
Keywords: tet_topic_shg; tet_topic_meta

Photonic crystal waveguides intersection for resonant quantum dot optical spectroscopy detection - Song, Xiaohong; Declair, Stefan; Meier, Torsten; Zrenner, Artur; Förstner, Jens (Optics Express)
Using a finite-difference time-domain method, we theoretically investigate the optical spectra of crossing perpendicular photonic crystal waveguides with quantum dots embedded in the central rod. The waveguides are designed so that the light mainly propagates along one direction and the cross talk is greatly reduced in the transverse direction. It is shown that when a quantum dot (QD) is resonant with the cavity, strong coupling can be observed via both the transmission and crosstalk spectrum. If the cavity is far off-resonant from the QD, both the cavity mode and the QD signal can be detected in the transverse direction since the laser field is greatly suppressed in this direction. This structure could have strong implications for resonant excitation and in-plane detection of QD optical spectroscopy.
Keywords: tet_topic_phc; tet_topic_qd

Near-field coupling and second-harmonic generation in split-ring resonator arrays - Grynko, Yevgen; Meier, Torsten; Linden, Stefan; Niesler, Fabian B. P.; Wegener, Martin; Förstner, Jens
We simulate the linear and nonlinear optical response from split-ring resonator (SRR) arrays to study collective effects between the constituent SRRs that determine spectral properties of the second harmonic generation (SHG). We apply the Discontinuous Galerkin Time Domain (DGTD) method and the hydrodynamic Maxwell-Vlasov model to calculate the SHG emission. Our model is able to qualitatively reproduce and explain the non-monotonic dependence of the spectral SHG transmission measured experimentally for SRR arrays with different lattice constants
Keywords: tet_topic_meta; tet_topic_shg

Engineering high harmonic generation in semiconductors via pulse shaping - Reichelt, Matthias; Hildebrandt, Andre; Walther, Andrea; Förstner, Jens; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XVI)
Paper Abstract High harmonic generation is investigated for a two-band model of a semiconductor nanostructure. Similar to an atomic two-level system, the semiconductor emits high harmonic radiation. We show how one can specifically enhance the emission for a given frequency by applying a non-trivially shaped laser pulse. Therefore, the semiconductor Bloch equations including the interband and additionally the intraband dynamics are solved numerically and the spectral shape of the input pulse is computed via an optimization algorithm. It is demonstrated that desired emission frequencies can be favored even though the overall input power is kept constant. We also suggest special metallic nano geometries to achieve enhanced localized optical fields. They are found by geometric optimization.
Keywords: tet_topic_shg

Tailoring the high-harmonic emission in two-level systems and semiconductors by pulse shaping - Reichelt, Matthias; Walther, Andrea; Meier, Torsten (Journal of the Optical Society of America B)
The generation of specific high harmonics for an optical two-level system is elucidated. The desired emitted radiation can be induced by a carefully designed excitation pulse, which is found by a multiparameter optimization procedure. The presented mechanism can also be applied to semiconductor structures for which the calculations result in much higher emission frequencies. The optimization procedure is either performed using a genetic algorithm or a rigorous mathematical optimization technique.

A graphene-based broadband optical modulator - Liu, Ming; Yin, Xiaobo; Ulin-Avila, Erick; Geng, Baisong; Zentgraf, Thomas; Ju, Long; Wang, Feng; Zhang, Xiang (Nature)

Towards the Origin of the Nonlinear Response in Hybrid Plasmonic Systems - Utikal, Tobias; Zentgraf, Thomas; Paul, Thomas; Rockstuhl, Carsten; Lederer, Falk; Lippitz, Markus; Giessen, Harald (Physical Review Letters)

Development of Bulk Optical Negative Index Fishnet Metamaterials: Achieving a Low-Loss and Broadband Response Through Coupling - Valentine, Jason; Zhang, Shuang; Zentgraf, Thomas; Zhang, Xiang (Proceedings of the IEEE)

Plasmonic Luneburg and Eaton lenses - Zentgraf, Thomas; Liu, Yongmin; Mikkelsen, Maiken H.; Valentine, Jason; Zhang, Xiang (Nature Nanotechnology)

The influence of charged InAs quantum dots on the conductance of a two-dimensional electron gas: Mobility vs. carrier concentration - Marquardt, B.; Beckel, A.; Lorke, A.; Wieck, A. D.; Reuter, Dirk; Geller, M. (Applied Physics Letters)

Many-body enhanced nonlinear conductance resonance in quantum channels - Han, Jong E.; Fischer, Saskia F.; Buchholz, Sven S.; Kunze, Ulrich; Reuter, Dirk; Wieck, Andreas D.; Bird, Jonathan P. (Physical Review B)

Dynamic Nuclear Spin Resonance inn-GaAs - Chen, Y. S.; Reuter, Dirk; Wieck, A. D.; Bacher, G. (Physical Review Letters)

Optical Control of Coherent Interactions between Electron Spins in InGaAs Quantum Dots - Spatzek, S.; Greilich, A.; Economou, Sophia E.; Varwig, S.; Schwan, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Reinecke, T. L.; Bayer, M. (Physical Review Letters)

Generation and detection of mode-locked spin coherence in (In,Ga)As/GaAs quantum dots by laser pulses of long duration - Spatzek, S.; Varwig, S.; Glazov, M. M.; Yugova, I. A.; Schwan, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Edge-induced magnetoplasmon excitation in a two-dimensional electron gas under quantum Hall conditions - Notthoff, Christian; Reuter, Dirk; Wieck, Andreas D.; Lorke, Axel (Physical Review B)

Resonant nuclear spin pumping in (In,Ga)As quantum dots - Cherbunin, R. V.; Flisinski, K.; Gerlovin, I. Ya.; Ignatiev, I. V.; Kuznetsova, M. S.; Petrov, M. Yu.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Electrostatically trapping indirect excitons in coupled InxGa1−xAs quantum wells - Schinner, G. J.; Schubert, E.; Stallhofer, M. P.; Kotthaus, J. P.; Schuh, D.; Rai, A. K.; Reuter, Dirk; Wieck, A. D.; Govorov, A. O. (Physical Review B)

Polarization-preserving confocal microscope for optical experiments in a dilution refrigerator with high magnetic field - Sladkov, Maksym; Bakker, M. P.; Chaubal, A. U.; Reuter, Dirk; Wieck, A. D.; van der Wal, C. H. (Review of Scientific Instruments)

Mode-filtered electron injection into a waveguide interferometer - Buchholz, Sven S.; Kunze, Ulrich; Reuter, Dirk; Wieck, Andreas D.; Fischer, Saskia F. (Applied Physics Letters)

Optically detected nuclear magnetic resonance in n-GaAs using an on-chip microcoil - Chen, Y. S.; Huang, J.; Reuter, Dirk; Ludwig, A.; Wieck, A. D.; Bacher, G. (Applied Physics Letters)

Transport spectroscopy of non-equilibrium many-particle spin states in self-assembled quantum dots - Marquardt, B.; Geller, M.; Baxevanis, B.; Pfannkuche, D.; Wieck, A. D.; Reuter, Dirk; Lorke, A. (Nature Communications)

Strong temperature destabilization of free exciton recombination in a two-dimensional structures with hole gas - Jadczak, J; Bryja, L; Wójs, A; Bartsch, G; Yakovlev, D R; Bayer, M; Plochocka, P; Potemski, M; Reuter, Dirk; Wieck, A (Journal of Physics: Conference Series)

Phonon-assisted exciton spin relaxation in (In,Ga)As/GaAs quantum dots - Kurtze, H.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (physica status solidi (c))

Structural, optical, and magnetic properties of Ho-implanted GaN thin films - Lo, F-Y; Guo, J-Y; Ney, V; Ney, A; Chern, M-Y; Melnikov, A; Pezzagna, S; Reuter, Dirk; Wieck, A D; Massies, J (Journal of Physics: Conference Series)

Towards the quantized magnetic confinement in quantum wires - Cerchez, M.; Tarasov, A.; Hugger, S.; Xu, Hengyi; Heinzel, T.; Zozoulenko, I. V.; Gasser-Szerer, U.; Reuter, Dirk; Wieck, A. D.; Ihm, Jisoon; Cheong, Hyeonsik

All-electrical transport spectroscopy of non-equilibrium many-particle states in self-assembled quantum dots - Marquardt, Bastian; Geller, Martin; Baxevanis, Benjamin; Pfannkuche, Daniela; Wieck, Andreas D.; Reuter, Dirk; Lorke, Axel; Ihm, Jisoon; Cheong, Hyeonsik

Electromagnetically induced transparency in low-doped n-GaAs - van der Wal, C. H.; Sladkov, M.; Chaubal, A. U.; Bakker, M. P.; Onur, A. R.; Reuter, Dirk; Wieck, A. D.; Ihm, Jisoon; Cheong, Hyeonsik

Manipulation of nuclear spin dynamics in n-GaAs using an on-chip microcoil - Chen, Y. S.; Huang, J.; Ludwig, A.; Reuter, Dirk; Wieck, A. D.; Bacher, G. (Journal of Applied Physics)

Vibrational properties of the LiNbO3 z-surfaces - Sanna, S.; Berth, Gerhard; Hahn, W.; Widhalm, A.; Zrenner, Artur; Schmidt, W. G. (IEEE Transactions on Ultrasonics, Ferroelectrics and Frequency Control)
The existence of localized vibrational modes both at the positive and at the negative LiNbO3 (0001) surface is demonstrated by means of first-principles calculations and Raman spectroscopy measurements. First, the phonon modes of the crystal bulk and of the (0001) surface are calculated within the density functional theory. In a second step, the Raman spectra of LiNbO3 bulk and of the two surfaces are measured. The phonon modes localized at the two surfaces are found to be substantially different, and are also found to differ from the bulk modes. The calculated and measured frequencies are in agreement within the error of the method. Raman spectroscopy is shown to be sensitive to differences between bulk and surface and between positive and negative surface. It represents therefore an alternative method to determine the surface polarity, which does not exploit the pyroelectric or piezoelectric properties of the material.

In situ characterization of ZnTe epilayer irradiation via time-resolved and power-density-dependent Raman spectroscopy - Wiedemeier, V; Berth, Gerhard; Zrenner, Artur; Larramendi, E M; Woggon, U; Lischka, K; Schikora, D (Semiconductor Science and Technology)
Laser irradiation damage in ZnTe epilayers was analyzed in situ by power-density-dependent and time-resolved micro-Raman spectroscopy. Damage by ablation or compound decomposition on the sample surface was revealed by the decrease of the ZnTe–nLO mode intensity with the increase of laser power density. The appearance of the peaks associated with the stronger crystalline-tellurium modes, tellurium aggregates and second-order Raman scattering at room temperature μ-Raman spectra was observed for higher power densities than 4.4 × 105 W cm−2. The Raman signal time transients of ZnTe–nLO and crystalline-tellurium modes reveal an exponential evolution of the laser irradiation damage and a fast formation of crystalline tellurium aggregates on the layer surface.

Characterization of SiON integrated waveguides via FTIR and AFM measurements - Frers, Torsten; Hett, Thomas; Hilleringmann, Ulrich; Berth, Gerhard; Widhalm, Alex; Zrenner, Artur (2011 Semiconductor Conference Dresden)
Silicon oxynitride (SiON) layers for telecommunication device application are grown by Plasma Enhanced Chemical Vapor Deposition (PECVD) for various gas compositions of SiH4, N2O and NH3. Processing and annealing effects on the oxynitride films were studied by Fourier Transform Infrared Spectroscopy (FTIR) and Atomic Force Microscopy (AFM) measurements. By reduction of the silane (SiH4) gas flow and enhancement of the PECVD deposition temperature, the absorption loss due to NH bands can be nearly completely erased. Furthermore the surface roughness can be reduced by decreasing the gas flow and rising the deposition temperature. First waveguide structures are introduced and their characterization is presented.

Room temperature spin relaxation length in spin light-emitting diodes - Soldat, Henning; Li, Mingyuan; Gerhardt, Nils C.; Hofmann, Martin R.; Ludwig, Arne; Ebbing, Astrid; Reuter, Dirk; Wieck, Andreas D.; Stromberg, Frank; Keune, Werner; Wende, Heiko (Applied Physics Letters)

Surface acoustic wave controlled carrier injection into self-assembled quantum dots and quantum posts - Krenner, Hubert J.; Völk, Stefan; Schülein, Florian J. R.; Knall, Florian; Wixforth, Achim; Reuter, Dirk; Wieck, Andreas D.; Kim, Hyochul; Truong, Tuan A.; Petroff, Pierre M. (physica status solidi (c))

Imaging of the Ferroelectric Domain Structures by Confocal Raman Spectroscopy - Berth, Gerhard; Hahn, Wjatscheslaw; Wiedemeier, Volker; Zrenner, Artur; Sanna, Simone; Schmidt, Wolf Gero (Ferroelectrics)
Confocal Raman spectroscopy was performed as an archetype imaging method to study the ferroelectric domain structure of periodically poled lithium niobate. More precisely, the linkage out of spatial resolution and spectral information proved itself as very useful. Here a specific modulation of the Raman lines by the local variation of polarity and a non-symmetric measuring-signal across the domain structure were found, which allows for imaging of domain boundaries as well as oppositely orientated domains. The high potential of this method is demonstrated by the visualization of the ferroelectric domain structures based on various phonon modes.
Keywords: Raman spectroscopy; ferroelectric domains; LiNbO3; confocal imaging

Electrically driven intentionally positioned single quantum dot - Mehta, Minisha; Reuter, Dirk; Wieck, Andreas D.; Michaelis de Vasconcellos, Steffen; Zrenner, Artur; Meier, Cedrik (physica status solidi (c))
Using a combined all-ultra-high-vacuum process employing lateral patterning with focused ion beams and molecular beam epitaxy, site-selective growth of single (In,Ga)As quantum dots is achieved. We have embedded such a layer of intentionally positioned quantum dots in the intrinsic region of a p-i-n junction so that the quantum dots can be driven electrically. In this contribution, we will present our results on the morphological properties of the ion-beam modified surface on which the quantum dot nucleation occurs together with a characterization of the electrical and optoelectronic properties. We will demonstrate that a single, individual quantum dot can directly be electrically addressed.
Keywords: molecular beam epitaxy; quantum dot; site control; electroluminescence

Lift-off of mesoporous layers by electrochemical etching on Si (100) substrates with miscut of 6° off towards (111) - Garralaga Rojas, E.; Terheiden, B.; Plagwitz, H.; Hensen, J.; Wiedemeier, V.; Berth, Gerhard; Zrenner, Artur; Brendel, R. (Thin Solid Films)
Uniform mesoporous Si double layers are formed on 4 inch p-type < 100> wafers with an off orientation of 6º towards < 111> by means of electrochemical etching in ethanoic-based HF electrolytes. These substrates are of interest for the epitaxial growth of III–V compound semiconductor stacks on their top for the production of multi-junction solar cells and very thin electronic devices. We demonstrate transfer of porous layers after an annealing process in hydrogen atmosphere. Electron Back-Scatter Diffraction analysis confirms that the substrate orientation is conserved during the etching and annealing steps. Confocal μ-Raman spectroscopy analysis shows a decrease in the Raman signal intensity after etching and a subsequent increase after annealing while no shift is observed. By means of Atomic Force Microscopy, analysis the surface appearance after the etching and annealing steps can be visualized. The mean surface roughness varies during the process from 0.55 nm for the unprocessed wafers to 0.27 nm after etching and 0.78 nm after annealing. The decrease of average roughness after etching is caused by an electropolishing step prior to porous formation. Despite of slight increase of mean surface roughness after annealing the samples are still appropriate for high quality epitaxial growth and subsequent lift-off.
Keywords: Porous Si; Layer transfer; Thin-film; Photovoltaics

Tailoring the photonic band splitting in metallodielectric photonic crystal superlattices - Utikal, Tobias; Zentgraf, Thomas; Tikhodeev, Sergei G.; Lippitz, Markus; Giessen, Harald (Physical Review B)

A Carpet Cloak for Visible Light - Gharghi, Majid; Gladden, Christopher; Zentgraf, Thomas; Liu, Yongmin; Yin, Xiaobo; Valentine, Jason; Zhang, Xiang (Nano Letters)

Investigations on the director field around microdisc resonators - Urbanski, Martin; Piegdon, Karoline A.; Meier, Cedrik; Kitzerow, Heinz-Siegfried (Liquid Crystals)

Liquid Crystal/Polymer Composites: Kinetic Study of the Grating Formation in Holographic Polymer-Dispersed Liquid Crystals - Redler, Andreas; Hoischen, Andreas; Kitzerow, Heinz-Siegfried (Molecular Crystals and Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Nanocomposites of a nematic liquid crystal doped with magic-sized CdSe quantum dots - Mirzaei, Javad; Urbanski, Martin; Yu, Kui; Kitzerow, Heinz-Siegfried; Hegmann, Torsten (Journal of Materials Chemistry)
Keywords: Materials Chemistry; General Chemistry

Electrooptic Switching in Graphene-Based Liquid Crystal Cells - Wahle, Markus; Kasdorf, Olga; Kitzerow, Heinz-Siegfried; Liang, Yanyu; Feng, Xinliang; Müllen, Klaus (Molecular Crystals and Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Efficient electro-optic switching in a photonic liquid crystal fiber - Lorenz, Alexander; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Numerical analysis of coupled photonic crystal cavities - Declair, S.; Meier, Torsten; Zrenner, Artur; Förstner, Jens (Photonics and Nanostructures - Fundamentals and Applications)
We numerically investigate the interaction dynamics of coupled cavities in planar photonic crystal slabs in different configurations. The single cavity is optimized for a long lifetime of the fundamental mode, reaching a Q-factor of ≈43, 000 using the method of gentle confinement. For pairs of cavities we consider several configurations and present a setup with strongest coupling observable as a line splitting of about 30 nm. Based on this configuration, setups with three cavities are investigated.
Keywords: tet_topic_phc

Application of the discontinous Galerkin time domain method to the optics of metallic nanostructures - Grynko, Yevgen; Förstner, Jens; Meier, Torsten (AAPP | Atti della Accademia Peloritana dei Pericolanti)
A simulation environment for metallic nanostructures based on the Discontinuous Galerkin Time Domain method is presented. The model is used to compute the linear and nonlinear optical response of split ring resonators and to study physical mechanisms that contribute to second harmonic generation.
Keywords: tet_topic_numerics; tet_topic_shg; tet_topic_meta

Intensity-dependent ultrafast dynamics of injection currents in unbiased GaAs quantum wells - Pochwała, Michał; Duc, Huynh Thanh; Förstner, Jens; Meier, Torsten (physica status solidi (RRL) - Rapid Research Letters)
The intensity dependence of optically-induced injection currents in unbiased GaAs semiconductor quantum wells grown in [110] direction is investigated theoretically for a number of well widths. Our microscopic analysis is based on a 14 x 14 band k . p method in combination with the multisubband semiconductor Bloch equations. An oscillatory dependence of the injection current transients as function of intensity and time is predicted and explained. It is demonstrated that optical excitations involving different subbands and Rabi flopping are responsible for this complex dynamics.
Keywords: tet_topic_qw

Oscillatory excitation energy dependence of injection currents in GaAs/AlGaAs quantum wells - Thanh Duc, Huynh; Förstner, Jens; Meier, Torsten; Priyadarshi, Shekhar; Racu, Ana Maria; Pierz, Klaus; Siegner, Uwe; Bieler, Mark (physica status solidi (c))
The injection of photocurrents by femtosecond laser pulses in (110)-orientedGaAs/AlGaAs quantum wells is investigated theoretically and experimentally. The roomtemperature measurements show an oscillatory dependence of the injection current amplitude and direction on the excitation photon energy. Microscopic calculations using the semiconductor Bloch equations that are set up on the basis of k.p band structure calculations provide a detailed understanding of the experimental findings.
Keywords: tet_topic_qw

Numerical investigation of the coupling between microdisk modes and quantum dots - Declair, S.; Meier, Torsten; Förstner, Jens (physica status solidi (c))
We numerically investigate the coupling between circular resonators and study strong light‐matter coupling of single as well as multiple circular resonators to quantum‐mechanical resonators in two dimensional model simulations. For all cases, the computed resonances of the coupled system as function of the detuning show anti‐crossings. The obtained mode splittings of coupled optical resonators are strongly depending on distance and cluster in almost degenerate eigenstates for large distances, as is known from coupled resonator optical waveguides. Vacuum Rabi splitting is observed for a quantum dot strongly coupled to eigenmodes of single perfectly cylindrical resonators.
Keywords: tet_topic_phc; tet_topic_microdisk

Simulation of the ultrafast nonlinear optical response of metal slabs - Wand, Mathias; Schindlmayr, Arno; Meier, Torsten; Förstner, Jens (Physica Status Solidi B)
We present a nonequilibrium ab initio method for calculating nonlinear and nonlocal optical effects in metallic slabs with a thickness of several nanometers. The numerical analysis is based on the full solution of the time‐dependent Kohn–Sham equations for a jellium system and allows to study the optical response of metal electrons subject to arbitrarily shaped intense light pulses. We find a strong localization of the generated second‐harmonic current in the surface regions of the slabs.
Keywords: tet_topic_shg

Localised Phonon Modes at LiNbO3(0001) Surfaces - Sanna, S.; Berth, Gerhard; Hahn, W.; Widhalm, A.; Zrenner, Artur; Schmidt, Wolf Gero (Ferroelectrics)
The vibrational properties of the LiNbO3 (0001) surfaces have been investigated both from first principles and with Raman spectroscopy measurements. Firstly, the phonon modes of bulk and of the (0001) surface are calculated by means of the density functional theory. Our calculations reveal the existence of localised vibrational modes both at the positive and at the negative surface. The surface vibrations are found at energies above and within the bulk bands. Phonon modes localised at the positive and at the negative surface differ substantially. In a second step, the Raman spectra of LiNbO3 bulk and of the two surfaces have been measured. Raman spectroscopy is shown to be sensitive to differences between bulk and surface and between positive and negative surface. The calculated and measured frequencies are in agreement within the error of the method.

Intensity dependence of optically-induced injection currents in semiconductor quantum wells - Pochwala, Michal; Duc, Huynh Thanh; Förstner, Jens; Meier, Torsten (CLEO:2011 - Laser Applications to Photonic Applications)
The intensity dependence of optically-induced injection currents in semiconductor quantum wells is investigated numerically. Oscillatory behavior of the electron charge current transients as function of intensity and time is predicted and explained.
Keywords: tet_topic_qw

Theoretical approach to the ultrafast nonlinear optical response of metal slabs - Wand, Mathias; Schindlmayr, Arno; Meier, Torsten; Förstner, Jens (CLEO:2011 - Laser Applications to Photonic Applications)
We present an ab-initio method for calculating nonlinear and nonlocal optical effects in metallic slabs with sub-wavelength thickness. We find a strong localization of the second-harmonic current at the metal-vacuum interface.
Keywords: tet_topic_shg

Injection currents in (110)-oriented GaAs/AlGaAs quantum wells: recent progress in theory and experiment - Duc, H. T.; Pochwala, M.; Förstner, Jens; Meier, Torsten; Priyadarshi, S.; Racu, A. M.; Pierz, K.; Siegner, U.; Bieler, M. (Ultrafast Phenomena in Semiconductors and Nanostructure Materials XV)
We experimentally and theoretically investigate injection currents generated by femtosecond single-color circularly-polarized laser pulses in (110)-oriented GaAs quantum wells. The current measurements are performed by detecting the emitted Terahertz radiation at room temperature. The microscopic theory is based on a 14 x 14 k • p band-structure calculation in combination with the multi-subband semiconductor Bloch equations. For symmetric GaAs quantum wells grown in (110) direction, an oscillatory dependence of the injection currents on the exciting photon energy is obtained. The results of the microscopic theory are in good agreement with the measurements.
Keywords: tet_topic_qw

Electron g-factor anisotropy in symmetric (110)-oriented GaAs quantum wells - Hübner, J.; Kunz, S.; Oertel, S.; Schuh, D.; Pochwała, M.; Duc, H. T.; Förstner, Jens; Meier, Torsten; Oestreich, M. (Physical Review B)
We demonstrate by spin quantum beat spectroscopy that in undoped symmetric (110)-oriented GaAs/AlGaAs single quantum wells, even a symmetric spatial envelope wave function gives rise to an asymmetric in-plane electron Land´e g-factor. The anisotropy is neither a direct consequence of the asymmetric in-plane Dresselhaus splitting nor a direct consequence of the asymmetric Zeeman splitting of the hole bands, but rather it is a pure higher-order effect that exists as well for diamond-type lattices. The measurements for various well widths are very well described within 14 × 14 band k·p theory and illustrate that the electron spin is an excellent meter variable for mapping out the internal—otherwise hidden—symmetries in two-dimensional systems. Fourth-order perturbation theory yields an analytical expression for the strength of the g-factor anisotropy, providing a qualitative understanding of the observed effects.
Keywords: tet_topic_qw

Application of the Discontinuous Galerkin Time Domain Method to the Optics of Bi-Chiral Plasmonic Crystals - Grynko, Yevgen; Förstner, Jens; Meier, Torsten; Radke, André; Gissibl, Timo; Braun, Paul V.; Giessen, Harald
A simulation environment for metallic nanostructures based on the Discontinuous Galerkin Time Domain method is presented. It is used to model optical transmission by silver bi‐chiral plasmonic crystals. The results of simulations qualitatively and quantitavely agree with experimental measurements of transmitted circular polarization.
Keywords: tet_topic_meta

Transformational Plasmon Optics - Liu, Yongmin; Zentgraf, Thomas; Bartal, Guy; Zhang, Xiang (Nano Letters)

Light-driven nanoscale plasmonic motors - Liu, Ming; Zentgraf, Thomas; Liu, Yongmin; Bartal, Guy; Zhang, Xiang (Nature Nanotechnology)

An Optical “Janus” Device for Integrated Photonics - Zentgraf, Thomas; Valentine, Jason; Tapia, Nicholas; Li, Jensen; Zhang, Xiang (Advanced Materials)

All-Liquid Photonic Microcavity Stabilized by Quantum Dots - Yim, Tae-Jin; Zentgraf, Thomas; Min, Bumki; Zhang, Xiang (Journal of the American Chemical Society)

Far-field measurement of ultra-small plasmonic mode volume - Zhang, Shuang; Park, Yong-Shik; Liu, Yongmin; Zentgraf, Thomas; Zhang, Xiang (Optics Express)

(100) GaAs/AlxGa1−xAs heterostructures for Zeeman spin splitting studies of hole quantum wires - Trunov, K.; Reuter, Dirk; Ludwig, A.; Chen, J.C.H.; Klochan, O.; Micolich, A.P.; Hamilton, A.R.; Wieck, A.D. (Journal of Crystal Growth)

Correlation-induced single-flux-quantum penetration in quantum rings - Giesbers, A. J. M.; Zeitler, U.; Katsnelson, M. I.; Reuter, Dirk; Wieck, A. D.; Biasiol, G.; Sorba, L.; Maan, J. C. (Nature Physics)

Observation of orientation- andk-dependent Zeeman spin-splitting in hole quantum wires on (100)-oriented AlGaAs/GaAs heterostructures - Chen, J C H; Klochan, O; Micolich, A P; Hamilton, A R; Martin, T P; Ho, L H; Zülicke, U; Reuter, Dirk; Wieck, A D (New Journal of Physics)

Electronic structure of self-assembled InGaAs/GaAs quantum rings studied by capacitance-voltage spectroscopy - Lei, W.; Notthoff, C.; Lorke, A.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Quantized Magnetic Confinement in Quantum Wires - Tarasov, A.; Hugger, S.; Xu, Hengyi; Cerchez, M.; Heinzel, T.; Zozoulenko, I. V.; Gasser-Szerer, U.; Reuter, Dirk; Wieck, A. D. (Physical Review Letters)

Spin dynamics of electrons and holes inInGaAs/GaAsquantum wells at millikelvin temperatures - Fokina, L. V.; Yugova, I. A.; Yakovlev, D. R.; Glazov, M. M.; Akimov, I. A.; Greilich, A.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Spin Noise of Electrons and Holes in Self-Assembled Quantum Dots - Crooker, S. A.; Brandt, J.; Sandfort, C.; Greilich, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review Letters)

Electronic structure of self-assembled InGaAs/GaAs quantum rings studied by capacitance-voltage spectroscopy - Lei, W.; Notthoff, C.; Lorke, A.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Control of the transmission phase in an asymmetric four-terminal Aharonov-Bohm interferometer - Buchholz, Sven S.; Fischer, Saskia F.; Kunze, Ulrich; Bell, Matthew; Reuter, Dirk; Wieck, Andreas D. (Physical Review B)

Nanostructures in p-GaAs with improved tunability - Csontos, M.; Komijani, Y.; Shorubalko, I.; Ensslin, K.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Full-wave rectification based upon hot-electron thermopower - Wiemann, M.; Wieser, U.; Kunze, U.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Enhanced Sequential Carrier Capture into Individual Quantum Dots and Quantum Posts Controlled by Surface Acoustic Waves - Völk, Stefan; Schülein, Florian J. R.; Knall, Florian; Reuter, Dirk; Wieck, Andreas D.; Truong, Tuan A.; Kim, Hyochul; Petroff, Pierre M.; Wixforth, Achim; Krenner, Hubert J. (Nano Letters)

Epitaxial growth and interfacial magnetism of spin aligner for remanent spin injection: [Fe/Tb]n/Fe/MgO/GaAs-light emitting diode as a prototype system - Schuster, E.; Brand, R. A.; Stromberg, F.; Ludwig, A.; Reuter, Dirk; Wieck, A. D.; Hövel, S.; Gerhardt, N. C.; Hofmann, M. R.; Wende, H.; Keune, W. (Journal of Applied Physics)

Evidence for localization and 0.7 anomaly in hole quantum point contacts - Komijani, Y.; Csontos, M.; Shorubalko, I.; Ihn, T.; Ensslin, K.; Meir, Y.; Reuter, Dirk; Wieck, A. D. (EPL (Europhysics Letters))

A two-dimensional electron gas as a sensitive detector to observe the charge carrier dynamics of self-assembled QDs - Marquardt, Bastian; Geller, Martin; Lorke, Axel; Reuter, Dirk; Wieck, Andreas D. (Physica E: Low-dimensional Systems and Nanostructures)

“Artificial Atoms” in Magnetic Fields: Wave-Function Shaping and Phase-Sensitive Tunneling - Lei, Wen; Notthoff, Christian; Peng, Jie; Reuter, Dirk; Wieck, Andreas; Bester, Gabriel; Lorke, Axel (Physical Review Letters)

Phase shifts and phaseπjumps in four-terminal waveguide Aharonov-Bohm interferometers - Kreisbeck, Christoph; Kramer, Tobias; Buchholz, Sven S.; Fischer, Saskia F.; Kunze, Ulrich; Reuter, Dirk; Wieck, Andreas D. (Physical Review B)

An intentionally positioned (In,Ga)As quantum dot in a micron sized light emitting diode - Mehta, M.; Reuter, Dirk; Wieck, A. D.; Michaelis de Vasconcellos, S.; Zrenner, A.; Meier, C. (Applied Physics Letters)

Capacitance-voltage spectroscopy on InAs quantum dot valence band states in tilted magnetic fields - Reuter, Dirk; Roescu, R; Zeitler, U; Maan, J C; Wieck, A D (Journal of Physics: Conference Series)

Optical probing of spin dynamics of two-dimensional and bulk electrons in a GaAs/AlGaAs heterojunction system - Rizo, P J; Pugzlys, A; Slachter, A; Denega, S Z; Reuter, Dirk; Wieck, A D; van Loosdrecht, P H M; van der Wal, C H (New Journal of Physics)

Oxygen sensing by fluorescence quenching of [Cu(btmgp)I] - Herres-Pawlis, Sonja; Berth, Gerhard; Wiedemeier, Volker; Schmidt, Ludger; Zrenner, Artur; Warnecke, Hans-Joachim (Journal of Luminescence)
A fluorescence study of acetonitrile solutions of bis(tetramethylguanidine)propane, copper(I)-iodide and [Cu(btmgp)I] was performed and the chemical reaction of the latter species with O2 was investigated at room temperature. The actual quenching process via O2 gassing was studied and an exponential dependence of the fluorescence intensity with respect to the complex concentration was observed. Furthermore the survey was deepened on time resolved fluorescence properties of solved [Cu(btmgp)I] in a wider concentration range. The applicability of this complex for O2 sensing inside a microreactor system was proven by confocal fluorescence measurements. It was shown that the investigated system can be used for oxygen sensing in the copper concentration range from 10−2 to 10−9 mol/l.
Keywords: Copper Oxygen Fluorescence quenching N donor ligands

Intensity enhancement of Te Raman modes by laser damage in ZnTe epilayers - Larramendi, E M; Berth, Gerhard; Wiedemeier, V; Hüsch, K-P; Zrenner, Artur; Woggon, U; Tschumak, E; Lischka, K; Schikora, D (Semiconductor Science and Technology)
Damage caused by laser irradiation on the surface of ZnTe epilayers was studied by micro-Raman and atomic force microscopy (AFM). ZnTe LO-phonon overtones up to four order and TO + (n − 1)LO zone-center phonons were observed in the resonant micro-Raman spectra at room temperature. Discrepancies in the literature regarding the origin of two features observed at low frequencies around 120 and 140 cm−1 in the Raman spectrum of ZnTe are discussed and resolved. These Raman peaks were not detected by using a low excitation laser power density on a Zn-terminated ZnTe surface; however, with the increase of the laser power density they were found to arise irreversibly. The correspondence of these peaks in a wave number with the strongest Raman peaks of the crystalline tellurium phase and the intensity enhancement behavior with the laser power in a similar way as for CdTe strongly suggests the formation of crystalline tellurium aggregates on the layer surface due to laser irradiation damage. AFM data reveal the occurrence of laser ablation on the ZnTe surface even though the surface temperature of the sample is below the melting point.

An intentionally positioned (In,Ga)As quantum dot in a micron sized light emitting diode - Mehta, M.; Reuter, Dirk; Wieck, A. D.; Michaelis de Vasconcellos, S.; Zrenner, Artur; Meier, Cedrik (Applied Physics Letters)
We have integrated individual (In,Ga)As quantum dots (QDs) using site-controlled molecular beam epitaxial growth into the intrinsic region of a p-i-n junction diode. This is achieved using an in situ combination of focused ion beam prepatterning, annealing, and overgrowth, resulting in arrays of individually electrically addressable (In,Ga)As QDs with full control on the lateral position. Using microelectroluminescence spectroscopy we demonstrate that these QDs have the same optical quality as optically pumped Stranski–Krastanov QDs with random nucleation located in proximity to a doped interface. The results suggest that this technique is scalable and highly interesting for different applications in quantum devices.

Intentionally positioned self-assembled InAs quantum dots in an electroluminescent p–i–n junction diode - Mehta, Minisha; Reuter, Dirk; Melnikov, Alexander; Wieck, Andreas D.; Michaelis de Vasconcellos, Steffen; Baumgarten, Tim; Zrenner, Artur; Meier, Cedrik (Physica E: Low-dimensional Systems and Nanostructures)
An intentional positioning of optically active quantum dots using site-selective growth by a combination of molecular beam epitaxy (MBE) and focused ion beam (FIB) implantation in an all-ultra-high-vacuum (UHV) setup has been successfully demonstrated. A square array of periodic holes on GaAs substrate was fabricated with FIB of 30 keV ions followed by an in situ annealing step. Subsequently, the patterned holes were overgrown with an optimized amount of InAs in order to achieve site-selective growth of the QDs on the patterned holes. Under well-optimized conditions, a selectivity of single quantum dot growth in the patterned holes of 52% was achieved. Thereafter, carrier injection and subsequent radiative recombination from the positioned InAs/GaAs self-assembled QDs was investigated by embedding the QDs in the intrinsic part of a GaAs-based p–i–n junction device. Electroluminescence spectra taken at 77 K show interband transitions up to the fifth excited state from the QDs.
Keywords: Molecular beam epitaxy; Focused ion beam; Self-assembled quantum dot; Electroluminescence

Resonant photocurrent-spectroscopy of individual CdSe quantum dots - Panfilova, M.; Michaelis de Vasconcellos, S.; Pawlis, A.; Lischka, K.; Zrenner, Artur (Physica E: Low-dimensional Systems and Nanostructures)
Here we report on investigations on CdSe quantum dots incorporated in ZnSe based Schottky photodiodes with near-field shadow masks. Photoluminescence and photocurrent of individual quantum dots were studied as a function of the applied bias voltage. The exciton energy of the quantum dot ground state transition was shifted to the excitation energy by using the Stark effect tuning via an external bias voltage. Under the condition of resonance with the laser excitation energy we observed a resonant photocurrent signal due to the tunnelling of carriers out of the quantum dots at electric fields above 500 kV/cm.
Keywords: CdSe/ZnSe quantum dots; Photodiode; Quantum confined Stark Effect; Photocurrent; II–VI Semiconductors

Extremely low-loss slow-light modes in plasmonic dielectric hybrid systems - Ishikawa, Atsushi; Oulton, Rupert F.; Zentgraf, Thomas; Zhang, Xiang (Plasmonics: Metallic Nanostructures and Their Optical Properties VIII)

Semiconductor plasmon laser - Sorger, Volker J.; Oulton, Rupert F.; Zentgraf, Thomas; Ma, Renmin; Gladden, Christopher; Dai, Lun; Bartal, Guy; Zhang, Xiang (Plasmonics: Metallic Nanostructures and Their Optical Properties VIII)

Controlled Etching Behavior of O-Polar and Zn-Polar ZnO Single Crystals - Mehta, M.; Meier, Cedrik (Journal of The Electrochemical Society)

Electroluminescence from silicon nanoparticles fabricated from the gas phase - Theis, Jens; Geller, Martin; Lorke, Axel; Wiggers, Hartmut; Wieck, Andreas; Meier, Cedrik (Nanotechnology)

Plasma modification of nanosphere lithography masks made of polystyrene beads - Gogel, D.; Weinl, M.; Lindner, Jörg; Stritzker, B. (JOURNAL OF OPTOELECTRONICS AND ADVANCED MATERIALS)
Nanosphere lithography (NSL) masks consisting of mono- or double-layers of polystyrene (PS) nano-beads are fabricated on silicon exploiting the self-organization of PS particles during the controlled drying of a colloidal suspension on a surface. The shape changes and shrinkage of PS sphere masks upon treatment in an air plasma are studied as a function of initial sphere size, plasma power and treatment time. The influence of several experimental parameters, including the plasma induced temperature rise, are analysed using scanning and transmission electron microscopy. It is demonstrated that a variety of new intriguing nanopatterns can be generated on silicon surfaces by the combination of NSL and plasma techniques, largely broadening the variety of patterns available so far by NSL.

Modellbasierte Bestimmung lokal gültiger Kinetiken chemischer Reaktionen in Flüssigphase mittels Flachbettmikroreaktor* - Warnecke, H.-J.; Bothe, D.; Zrenner, Artur; Berth, Gerhard; Hüsch, K.-P. (Chemie Ingenieur Technik)
Strömungsbasierte Mischprozesse sind grundlegender Bestandteil vieler chemischer Prozesse. Realisierbare Mischzeiten reichen von einigen Millisekunden bis zu Sekunden, wobei die vollständige Homogenisierung oft nicht sichergestellt ist. Werden kinetische Parameter chemischer Reaktionen dieses Zeitskalenbereichs ohne Berücksichtigung der Mischprozesse bestimmt, sind sie mischungsmaskiert und geben die inhärente chemische Kinetik nicht wieder. In dieser Arbeit wird die Validierung und Anwendung einer Methode zur Bestimmung inhärenter chemischer Kinetiken von in Flüssigphase ablaufenden chemischen Reaktionen im stationären, laminaren Flachbettmikroreaktor vorgestellt. Der verfolgte Ansatz basiert auf der mechanistischen Modellierung der Molmengen unter Berücksichtigung von Konvektion, Diffusion und Reaktion und der Bestimmung der unbekannten Parameter durch Anpassung des Modells an experimentell ermittelte Konzentrationsverläufe.

Self-assembled quantum dots in a liquid-crystal-tunable microdisk resonator - Piegdon, Karoline A.; Offer, Matthias; Lorke, Axel; Urbanski, Martin; Hoischen, Andreas; Kitzerow, Heinz-Siegfried; Declair, Stefan; Förstner, Jens; Meier, Torsten; Reuter, Dirk; Wieck, Andreas D.; Meier, Cedrik (Physica E: Low-dimensional Systems and Nanostructures)

Director field of birefringent stripes in liquid crystal/nanoparticle dispersions - Urbanski, Martin; Kinkead, Brandy; Hegmann, Torsten; Kitzerow, Heinz-Siegfried (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Blue Phases: Prior Art, Potential Polar Effects, Challenges - Kitzerow, Heinz-Siegfried (Ferroelectrics)
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

33. Arbeitstagung Flüssigkristalle - Kitzerow, Heinz-Siegfried (Nachrichten aus der Chemie)
Keywords: General Chemical Engineering; General Chemistry

Liquid Crystal Addressing by Graphene Electrodes Made from Graphene Oxide - Nordendorf, Gaby; Kasdorf, Olga; Kitzerow, Heinz-Siegfried; Liang, Yanyu; Feng, Xinliang; Müllen, Klaus (Japanese Journal of Applied Physics)
The electrooptic characteristics of the field-induced reorientation of a nematic liquid crystal are studied using graphene layers as transparent conductive electrodes. The covering of a large area with highly conductive graphene was achieved by the thermal reduction of a graphene oxide film. The conductivity of the graphene electrode provides electrooptic properties that are comparable to those of liquid crystal cells with two conventional indium tin oxide electrodes. This result confirms earlier studies and suggestions concerning graphene-based liquid crystal devices. It demonstrates that the fabrication of graphene layers via the deposition and subsequent reduction of graphene oxide is suitable for liquid crystal applications.
Keywords: General Physics and Astronomy; General Engineering

Electroconvection in nematic liquid crystals via nanoparticle doping - Urbanski, Martin; Kinkead, Brandy; Qi, Hao; Hegmann, Torsten; Kitzerow, Heinz-Siegfried (Nanoscale)
Keywords: General Materials Science

Switchable waveguiding in two liquid-crystal-filled photonic crystal fibers - Lorenz, Alexander; Schuhmann, Rolf; Kitzerow, Heinz-Siegfried (Applied Optics)